"Just Call Me a Desert Researcher". Issue 2 (August 2017) - Heimlich, Rüdiger
Abstract: Whether in documentary films, exhibitions, talks or articles, for decades the Cologne‐based geologist and climate scientist Stefan Kröpelin has been popularising the history, landscapes and people of the Sahara. As a field researcher and in many ways a "science ambassador", the DFG and the Stifterverband have chosen him as the recipient of this year's Communicator Award.